Idiopathic interstitial pneumonia or idiopathic interstitial pneumonitis: what's in a name?. Issue 2 (14th February 2019) - Wells, Athol U.; Brown, Kevin K.; Flaherty, Kevin R.; Kolb, Martin; Thannickal, Victor J.
We congratulate L. Kolilekas and co-workers on their closely argued plea to resolve semantic imprecision in a field that suffers from a surfeit of acronyms. We can only agree that the "idiopathic interstitial pneumonia" (IIP) label should be discussed forensically. Meaningful reappraisal of IIP terminology requires a major international initiative with, crucially, the presentation of arguments for proposed change to all group members with the opportunity for written responses, in advance of face to face discussion. This model is seldom applied in expert group discussions, which are sometimes perfunctory due to time constraints, especially when held during major world meetings. The current proposal can be seen as the correct initiation of changes that are likely to be hotly debated due to a pivotal difficulty, discussed below. We welcome debate on the implications of a change from "pneumonia" to "pneumonitis", but suggest that this alteration does not capture a unifying pathogenetic basis for these diverse disorders http://ow.ly/yMIA30ns2q0